Eat that frog! : 21 great ways to stop procrastinating and get more done in less time - Tracy, Brian (Berrett-Koehler Publishers, Inc., 2017)
Stop Procrastinating Get More of the Important Things Done--Today! There just isn't enough time for everything on our to-do list--and there never will be. Successful people don't try to do everything. They learn to focus on the most important tasks and make sure those get done. They eat their frogs. There's an old saying that if the first thing you do each morning is eat a live frog, you'll have the satisfaction of knowing you're done with the worst thing you'll have to do all day. For Tracy, eating a frog is a metaphor for tackling your most challenging task--but also the one that can have the greatest positive impact on your life. Eat That Frog! shows you how to organize each day so you can zero in on these critical tasks and accomplish them efficiently and effectively. In this fully revised and updated edition, Tracy adds two new chapters. The first explains how you can use technology to remind yourself of what is most important and protect yourself from what is least important. The second offers advice for maintaining focus in our era of constant distractions, electronic and otherwise. But one thing remains unchanged: Brian Tracy cuts to the core of what is vital to effective time management: decision, discipline, and determination. This life-changing book will ensure that you get more of your important tasks done--today!